MENGEMBANGKAN KEMAMPUAN KOGNITIF MELALUI MEDIA BAHAN KARDUS BENTUK GEOMETRI DI RA UMMI KULSUM CITAMIANG KOTA SUKABUMI - Kori Sundari; Nia Permanik (Jurnal El-Audi, 2022)
Cognitive is a thought process and relates to the level of intelligence which is largely determined by the manipulation and active interaction of children with the environment, namely the ability to connect, assess and consider an event or events. The purpose of this study was to find out how to develop cognitive abilities through geometrical cardboard materials at RA Ummi Kulsum Citamuang, Sukabumi City. This study uses a descriptive qualitative research with the research subject is class B children, totaling 17 students and 2 teachers. Data collection tools in this study are observation, interviews (interviews) and documentation. Data were analyzed using data reduction, data display and verification/drawing conclusions. The results of the study can be concluded that the cognitive development of grade B children at RA Ummi Kulsum Citamuang, Sukabumi City has a very large influence through the media of cardboard geometric shapes by paying attention to the design of activities and achievement indicators that are in accordance with the cognitive development of early childhood, namely choosing the theme to be achieved. , determine the tools and materials needed in the activity, determine the steps in the activity, divide the children into several groups and determine the tasks that the child will do. Of the 17 participants, 64.7% of children's cognitive development began to develop through geometrical cardboard materials.